Occupational Differences in Psychological Distress Between Chinese Dentists and Dental Nurses - Zhang, Yingying; Yan, Li; Long, Huiqing; Yang, Lu; Wang, Jing; Liu, Yiyun; Pu, Juncai; Liu, Li; Zhong, Xiaogang; Xin, Jin (Frontiers in Psychology, 2022)
Background Doctors and allied health professionals are facing serious mental health issues, which have received widespread attention. This study aimed to explore the occupational differences in psychological distress between Chinese dentists and dental nurses. Materials and Methods The data was collected from a cross-sectional study conducted by the Chongqing Stomatological Association. Medical personnel involved in this survey were invited to complete a battery of self-administrated questionnaires, specifically the General Health Questionnaire-12, Maslach Burnout Inventory, and career choice regret scale. Data on demographic characteristics and working conditions were also collected. The results of these questionnaires were analyzed with SPSS (version 23.0). Univariate and multivariable analyzes were conducted to explore the influencing factors. Results A total of 3,020 valid questionnaires, including 1,855 dentists and 1,165 dental nurses, were collected from 11 provinces of China. In general, 23.8% of responders exhibited psychological distress. The rate of dentists was 25.7%, and that of dental nurses was 20.8%. The prevalence was 4.9% higher in dentists than in dental nurses (P < 0.05). The multivariable analysis showed that factors associated with psychological distress for dentists were lower income, burnout, high job stress, career-choice regret, and lack of sufficient personal time, and that for dental nurses were age, lower income, longer working hours per week, burnout, high job stress, low job satisfaction, lack of sufficient personal time, and poor medical environment. Conclusion The prevalence of psychological distress was relatively high among dental medical staff, and dentists showed a higher prevalence than dental nurses. Nurses have more risk factors for psychological distress than dentists. These results indicate that it is necessary to monitor the mental health status of dental medical staff and implement accurate strategies for dentists and dental nurses to promote their physical and mental health.